Optimization and Validation of a Custom-Designed Perfusion Bioreactor for Bone Tissue Engineering: Flow Assessment and Optimal Culture Environmental Conditions - Yamada, Shuntaro; Yassin, Mohammed A.; Schwarz, Thomas; Mustafa, Kamal; Hansmann, Jan (Frontiers in Bioengineering and Biotechnology, 2022)
Various perfusion bioreactor systems have been designed to improve cell culture with three-dimensional porous scaffolds, and there is some evidence that fluid force improves the osteogenic commitment of the progenitors. However, because of the unique design concept and operational configuration, the experimental setups of perfusion bioreactor systems are not always compatible. To reconcile results from different systems, the thorough optimisation and validation of the experimental configuration are required in each system. In this study, optimal experimental conditions for a perfusion bioreactor were explored in 3 steps. First, an in silico modelling was performed using a scaffold geometry obtained by microCT and an expedient geometry parameterised with porosity and permeability to assess the accuracy of calculated fluid shear stress and computational time. Then, environmental factors for cell culture were optimised, including the volume of the medium, bubble suppression, and medium evaporation. Further, by combining the findings, it was possible to determine the optimal flow rate at which cell growth was supported but osteogenic differentiation was triggered. Here, we demonstrated that fluid shear stress, ranging from nearly 0 to 15 mPa, was sufficient to induce osteogenesis, but cell growth was severely impacted by the volume of perfused medium, the presence of air bubbles, and medium evaporation, all of which are common concerns in perfusion bioreactor systems. This study emphasises the necessity of optimisation of experimental variables, which may often be underreported or overlooked, and indicates steps which can be taken to address issues common to perfusion bioreactors for bone tissue engineering.